Evaluating Monetary Policy of Central Bank of Syriato target inflation during the period 2011-2022 (Damascus University Journal for the economic and Political sciences, 2026)
During the period between 2011 and 2022, the Syrian economy recorded high inflation rates, due to the significant decline in supply due to the significant decline in output, the decline in the exchange rate of the Syrian Pound, the damage to foreign trade as a result of economic sanctions and the war on Syria, and the worsening general budget deficit and its financing through direct lending from the Central Bank in light of a high level of spending and deteriorating public revenues. Here, the study aimed to evaluating monetary Policy of Central Bank of Syria to target inflation.The quantitative approach was adopted in light of the study variables, represented by credit instruments, interest rates, and exchange rates, as independent variables, and the inflation rate as a dependent variable. The data was processed on the basis of time series of variables (panel data) and their impact on the dependent variable was tested using the EViews version 12.The study concluded with a set of results, the most important of which was the presence of a statistically significant effect of using the interest rate tool as one of the monetary policy tools in treating the phenomenon of inflation, as the relationship was inverse between the interest rate and inflation, and the presence of a statistically significant effect of using the exchange rate as one of the monetary policy tools in Treating the phenomenon of inflation, as the relationship between the exchange rate and inflation was positive, as well as the existence of a statistically significant effect of using the credit tool as one of the monetary policy tools in treating the phenomenon of inflation in the Syrian economy, and the relationship between credit and inflation was positive.
Keywords: Central Bank of Syria; Monetary Policy; Exchange Rate; Credit Instrument; Interest Rate; Inflation